Discriminating between impact or nonimpact origin of small meteorite crater candidates: No evidence for an impact origin for the Tor crater, Sweden. (17th October 2022) - Plado, Jüri; Losiak, Ania; Jõeleht, Argo; Ormö, Jens; Alexanderson, Helena; Alwmark, Carl; Wild, Eva Maria; Steier, Peter; Awdankiewicz, Marek; Belcher, Claire
Abstract: Compared to intensive research on km‐sized meteorite impact craters, fewer studies focus on smaller craters. The small craters are often hard or impossible to recognize using "classical" criteria like the presence of shatter cones, shocked quartz, and geochemical indicators. Therefore, a long list of candidate structures awaiting approval/disapproval of their origin has been formed over the last decades. One of them is the Tor structure in central Sweden. To test a hypothesis of an impact origin of this structure, we have performed topographical analysis, geophysical studies, 10 Be exposure dating of boulders, and 14 C dating of Tor‐associated charcoal. None of the methods gave us a reason to claim the Tor structure is of impact origin. Thus, we support a recently suggested idea of Tor being formed by a grounded iceberg within a glacial lake.